Impact of COVID19 towards Hotel Industry in Malaysia - ZULKARNAIN, SITI HAFSAH; Mohd Azuan Mohd Alias2; Zakiyah Hasan; Mustafa Kamal Mat; Abdol Samad Nawi (Journal Of Management Analytical and Solution (JoMAS), 2022)
The hotel industry is one of the important economic sectors as a driver of national economic growth as large investments continue to flow into its development around the world. Therefore, the tourism sector is an important driver that affects the economy of a country. The main objective of this research is to identify the relationship between the hotel industry and the impact of COVID-19 on economic growth in Malaysia. Findings obtained from this research of previous studies show that the COVID-19 pandemic has had a huge impact and may collapse the operating system of the hotel industry. Based on the comprehensive review of the related literature this research finds that the key issues and challenges faced by the COVID-19 pandemic in the Malaysian hotel industry, lessons learned from its devastating effects on the industry, and to contemplate possible solutions and strategies for post-pandemic recovery from a global perspective. A more comprehensive management strategy and method is needed in rebuilding the hotel industry post COVID-19 pandemic that hit the whole world